The Impact of Mobile Banking Applications on Customer Satisfaction: A Case Study of BSI Mobile - Zulfikar Fauzi; Muhammad Fikry Januar; Rosena Shintabella (Politeknik Mardira Indonesia, 2025)
The Sharia economy continues to grow in Indonesia, particularly in the banking sector, such as BSI (Bank Syariah Indonesia). In addition, the era of Industrial Revolution 4.0 gave rise to many innovations in the field of financial services (financial technology). The high number of internet and mobile phone users in Indonesia supports the adoption of technology in the financial sector, which is facilitated by the BSI Mobile application, enabling customers to transact more easily. Therefore, this study looks at the impact of the BSI Mobile application on customer satisfaction in terms of speed, security, accuracy, and trust. This research collects primary data from 113 active bank customers of BSI in Majalengka, West Java. The findings show that the BSI Mobile application contributes to customers’ satisfaction. This research also found that customers with higher education are more likely to have higher satisfaction with the BSI Mobile application.